Pengaruh Lingkungan Kerja, Karakteristik Individu Dan Budaya Organisasi Terhadap Kinerja Karyawan (Studi Kasus : Ratu Swalayan Departemen Store Kota Malang) - Mulyani, Dwi Indah; Susyanti, Jeni; Sholehuddin, Sulton (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to determine the influence of the work environment, individual characteristics, and organizational culture on employee performance at Ratu Swalayan Department Store in Malang City. The research method used was a quantitative approach with multiple linear regression analysis. Sampling was conducted using a saturated sampling technique with 30 respondents. The results indicate that all three independent variables simultaneously have a significant effect on employee performance. Partially, organizational culture has the most dominant influence on improving employee performance. Keywords: Work Environment, Individual Characteristics, Organizational Culture, Employee Performance